One-minute discipline : classroom management strategies that work - Bianco, Arnie (San Francisco : Jossey-Bass, 2002)
Contains over one hundred one-minute techniques, strategies, and support ideas designed to help teachers manage classroom behavior,each presented on a reproducible page, grouped by topic in ten sections, including philosophy, vocabulary, the first week of school, and others.
Includes bibliographical references (p. 251-252).
Professional
Keywords: Classroom management -- Handbooks, manuals, etc; Teacher effectiveness -- Handbooks, manuals, etc; Classroom management -- Handbooks, manuals, etc; Teaching -- Handbooks, manuals, etc